Effect of pH on Brazilin Extraction from Sappanwood (Caesalpinia sappan L.) and Its Impact on the Efficiency of Natural Dye-Sensitized Solar Cells (DSSCs) - Al Hafidl, Achmad Naufal; Nita Kusumawati; Pirim Setiarso; Samik, Samik; Maria Monica Sianita Basukiwardojo; Khofifatul Rahmawati (Science and Technology Indonesia, 2026)
Dye-sensitized solar cells (DSSCs) are a sustainable photovoltaic technology for addressing the global energy crisis through the conversion of solar energy using photosensitive dyes. This study aims to investigate the effect of pH variation during extraction on the optical, electrochemical, and photovoltaic characteristics of brazilin dye from sappanwood (Caesalpinia sappan L.) for DSSC applications. Brazilian extraction was performed using Microwave-Assisted Extraction (MAE) with pH conditioning from 2 to 12. UV-Vis spectroscopy showed an increase in light absorbance at 400–800 nm. The pH 8 dye exhibited a maximum absorption peak at 444.59 nm due to the formation of a quinoidal base through partial deprotonation of the hydroxyl (-OH) group. FTIR characterization confirmed the chemical structure of the dye with characteristic absorption spectra of broad bands at 3000–3500 cm-1 for the phenolic hydroxyl group and peaks at 2800–3000 cm-1 for aromatic C-H stretching vibrations, as well as aromatic C=C and C=O stretching vibrations at 1600–1400 cm-1. Energy band gap analysis revealed that the dye at pH 2–12 has an energy gap range of 0.1788–0.5355 eV. Optimizing the extraction pH revealed that pH 8 yields the most effective dye performance, resulting in a peak DSSC efficiency of 2.17%, a minimal charge transfer resistance of 100 Ω, and the narrowest energy bandgap at 0.1788 eV. Weakly basic conditions enhance dye molecule conjugation, strengthen bonding with TiO2, and optimize the overall charge transfer process. The research findings confirm the potential of optimizing natural dye extraction conditions as a strategy to enhance DSSC efficiency in a sustainable and environmentally friendly manner.